Alternative splicing and expression analysis of High expression of osmotically responsive genes1 (HOS1) in Arabidopsis - Jeong Hwan Lee, Soo Hyun Kim, Jae Joon Kim & Ji Hoon Ahn* (BMB Reports, 2012)
High expression of osmotically responsive genes1 (HOS1), akey regulator of low temperature response and flowering time,encodes an E3 ubiquitin ligase in Arabidopsis. Here, we reportcharacterization of a newly identified splice variant (HOS1-L)of HOS1. Comparative analyses revealed that HOS1-L has alonger 5' nucleotide sequence than that of the previouslyidentified HOS1 (HOS1-S) and that its protein sequence wasmore conserved than that of HOS1-S in plants. HOS1-Ltranscripts were spatio-temporally more abundant than thoseof HOS1-S. The recovery rate of HOS1-S expression was fasterthan that of HOS1-L after cold treatment. Diurnal oscillationpatterns of HOS1-L revealed that HOS1-L expression wasaffected by photoperiod. An in vitro pull-down assay revealedthat the HOS1-L protein interacted with the ICE1 protein.HOS1-L overexpression caused delayed flowering in wild-typeplants. Collectively, these results suggest regulation of HOS1expression at the post-transcriptional level.